(untitled) (Quaestiones Disputatae: temas en debate, 2021)
This paper uses the documentary-bibliographic method to describe and develop, from an exegetical approach, crucial elements within the studies on Hannah Arendt, namely, the way in which it is possible to understand the freedom-responsibility relationship within the conceptual network that implies the theory of action and natality in this author. In order to achieve this objective, the article is divided into three parts: on the one hand, in the first two sections, the concept of freedom and responsibility are conceptually developed; on the other, a comparative-relational work is developed in which it is hoped to place both concepts in correspondence with the rest of Arendt’s theoretical-conceptual scaffolding. Thus, a reinterpretation of this conceptual duo is sought from what the author postulates.